The Effects of Angiotensin II on Renal Water and Electrolyte Excretion in Normal and Caval Dogs - Porush, Jerome G. (1967)
The effects of intravenous administration of angiotensin II on renal water and electrolyte excretion were examined during hydropenia, water diuresis, and hypotonic saline diuresis in anesthetized normal dogs and dogs with thoracic inferior vena cava constriction and ascites (caval dogs). The effects of unilateral renal artery infusion of a subpressor dose were also examined. During hydropenia angiotensin produced a decrease in tubular sodium reabsorption, with a considerably greater natriuresis in caval dogs, and associated with a decrease in free water reabsorption (T(c)(H(2)O)). Water and hypotonic saline diuresis resulted in an augmented angiotensin natriuresis, with a greater effect still observed in caval dogs. In these experiments free water excretion (C(H(2)O)) was limited to 8-10% of the glomerular filtration rate (GFR), although distal sodium load increased in every instance. In the renal artery infusion experiments a significant ipsilateral decrease in tubular sodium reabsorption was induced, particularly in caval dogs. These findings indicate that angiotensin has a direct effect on renal sodium reabsorption unrelated to a systemic circulatory alteration. The attenuation or prevention of the falls in GFR and effective renal plasma flow (ERPF) usually induced by angiotensin may partially account for the greater natriuretic response in caval dogs and the augmentation during water or hypotonic saline diuresis. However, a correlation between renal hemodynamics and the degree of natriuresis induced was not always present and, furthermore, GFR and ERPF decreased significantly during the intrarenal artery infusion experiments. Therefore, the present experiments indicate that another mechanism is operative in the control of the angiotensin natriuresis and suggest that alterations in intrarenal hemodynamics may play a role. The decrease in T(c)(H(2)O) and the apparent limitation of C(H(2)O) associated with an increase in distal sodium load localize the site of action of angiotensin to the ascending limb of Henle's loop and the proximal tubule.